SAMARQAND VILOYATI O‘RTA MAXSUS, KASB-HUNAR TA’LIMI SOHASIDAGI XALQARO ALOQALARI (1991-2016 YY). - Fayzullayeva Shaxnoza Baxriddinova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  analyzes  the  establishment,  development,  and shortcomings  of  vocational  colleges  in  the  Samarkand  region  during  the  years  of independence, based on cooperation with international organizations such as the UN, the World Bank, the European Bank for Reconstruction and Development, and the Asian Development Bank.